ANALISIS DAMPAK HARGA DAN FASILITAS PADA KEPUASAN WISATAWAN OCARINA BATAM - Benget Rosalina; Arina Luthfini Lubis (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to analyze the influence of price and facilities on visitor satisfaction at Ocarina Batam Tourism. The research background was based on tourists’ complaints regarding the imbalance between ticket prices and the quality of facilities. A quantitative approach with a survey method was conducted on 60 purposively selected respondents. The research instrument was a Likert-scale questionnaire, and the data were analyzed using multiple linear regression. The findings reveal that both price and facilities significantly and positively affect visitor satisfaction, either partially or simultaneously. Facilities were identified as the dominant factor, having a higher regression coefficient compared to price. Together, the two variables explained 81.8% of the variation in visitor satisfaction. These results highlight the importance of aligning pricing strategies with facility improvements in order to enhance visitor satisfaction and loyalty.